Construction of a User-Led Resource for People Transitioning to Secondary Progressive Multiple Sclerosis: Results of an International Nominal Group Study - Giovannetti, Ambra Mara; Barabasch, Anna; Giordano, Andrea; Quintas, Rui; Barello, Serena; Graffigna, Guendalina; Alfieri, Sara; Schiffmann, Insa; Muche-Borowski, Cathleen; Borreani, Claudia; Heesen, Christoph; Solari, Alessandra; et al. (Frontiers in Neurology, 2020)
Background: ManTra is a mixed-methods, co-production research project for developing an intervention (resource) for people with newly-diagnosed secondary progressive multiple sclerosis (pwSPMS) in Italy and Germany. In previous project actions, six resources were outlined, meeting the needs prioritized by pwSPMS. Aims: To achieve multiple-stakeholder consensus on the most suitable resource; to refine the consensus resource. Methods: Two nominal group technique (NGT) meetings were held, one in Milan and one in Hamburg. Participants were pwSPMS (5 in Italy/6 in Germany), pwSPMS significant others (SOs, 4/5), healthcare professionals (HPs, 7/4) and health service researchers/patient and citizen organizations representatives (HPCORs, 5/5). Two of the four resources discussed in each meeting were the same in Italy and Germany: ‘Promoting the engagement of pwSPMS: a program for the patients and the HPs’ and ‘Enriched physiotherapy program for pwSPMS’. The other two were ‘A personalized care plan for pwSPMS’ and ‘Roadmap for social and economic benefits’ in Italy, and ‘Metacognitive and everyday life training for pwSPMS’ and ‘Psychological support for pwSPMS’ in Germany. Each meeting consisted of two plenary sessions, and a parallel group session (four stakeholder groups: pwSPMS, SOs, HPs, HPCORs) in between. Meetings’ narratives were analyzed thematically. Results: The two meetings were rich in participation and discussion. In Italy, the consensus resource was ‘A personalized care plan for pwSPMS’. Refinements included enrichment with pwSPMS engagement, inclusion of additional HPs, improved definition of the MS nurse’s role within the interdisciplinary panel, and community care integration. In Germany, the consensus resource was ‘Psychological support for pwSPMS’. Refinements included reshaping this resource into a more comprehensive and adaptive rehabilitation intervention, and training the psychologist in recognizing client’s rehabilitative needs and enhancing his/her autonomy. Conclusions: The NGT eased multiple-stakeholder deliberation and resource fine-tuning in both countries.